Types of tourism and their classification in the context of modern trends of tourism industry development. (Economics and region, 2017)
UDC 338.48:339Anna Romanova, PhD (Economics). Chernihiv National Technologic University. Types of tourism and their classification in the context of modern trends of tourism industry development. The author analyzes in the article main types of tourism in the context of modern trends of tourism industry development. The classification of tourism types has been proposed on the bases of the dominant features, such as: benefits for the economy of the country; purposes of travel; socio-demographic characteristics of consumers; sources of financing; mode of movement; geography of directions; type of booking a tour; duration of a tour; the subject of a tour organization; number of tourists; legality etc. The new types of tourism that appeared in the recent decades have been explored. The definition of modern types of tourism has been formulated. Certain factors that influence the popularity of certain types of tourism & travel and contribute to the emergence of new types of tourism have been identified. These are: global trends in consumption and development of the services market; domination of the impressions industry; informatization of society, transition to the online-space; socio-demographic change a tourist portrait of; the cult of a healthy lifestyle, the trend of healthy life and longevity; a request for environmental consumption and livelihoods; military and political conflicts, the threat of terrorist attacks, natural disasters, the development of virtual tours etc. The emergence of new types of tourism, as well as changes in the structure of the distribution of the tourism market by species should necessarily be considered to meet different consumer needs, for effective strategic planning, as well as a deeper analysis of the functioning of the tourism industry. Keywords: international tourism, types of tourism, classification of tourism types, tourism industry.